2009
DOI: 10.1136/jnnp.2008.165720
|View full text |Cite
|
Sign up to set email alerts
|

Association between 25-hydroxyvitamin D levels and cognitive performance in middle-aged and older European men

Abstract: In this study, lower 25(OH)D levels were associated with poorer performance on the DSST. Further research is warranted to determine whether vitamin D sufficiency might have a role in preserving cognitive function in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 42 publications
(48 reference statements)
4
92
2
2
Order By: Relevance
“…Eight cross-sectional and case-control studies, which included data from 2749 participants, contributed to this analysis. Taken together, these studies showed a higher average MMSE score in participants with higher VD concentrations [7,31,32]. The role of VD in skeletal health is well established, but more recent findings have also linked VD deficiency to a range of non-skeletal conditions such as cardiovascular disease, cancer, stroke and metabolic disorders including diabetes.…”
Section: Discussionmentioning
confidence: 73%
“…Eight cross-sectional and case-control studies, which included data from 2749 participants, contributed to this analysis. Taken together, these studies showed a higher average MMSE score in participants with higher VD concentrations [7,31,32]. The role of VD in skeletal health is well established, but more recent findings have also linked VD deficiency to a range of non-skeletal conditions such as cardiovascular disease, cancer, stroke and metabolic disorders including diabetes.…”
Section: Discussionmentioning
confidence: 73%
“…A study using the data of the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2006 found no relationship between the vitamin D level and depression [6]. However, a study of 3,369 people aged 40~79 in Europe conducted in 2009 and a prospective cohort study in the United States conducted in 2010 reported that the lower the level of vitamin D was, the higher the level of depression was [7,8]. In Korea, the relationship between vitamin D and depression was analyzed by the data of the Korean National Health and Nutrition Examination Survey (KNHANES) conducted from 2008 to 2010, and no association was found [9].…”
Section: The Need For Researchmentioning
confidence: 99%
“…Özellikle ileri yaşlarda düşük vitamin D seviyelerinin, demansla ilişkisi oldukça yüksek olan hafıza ve yönetici fonksiyonlarda gerilemeye neden olduğu gösterilmiştir (10)(11)(12). Ancak bu bilginin daha erken yaşlarda doğruluğu ile ilgili veriler yetersizdir (2,13,14). Bu nedenle, vitamin D düzeyi düşük olan erişkin kadınlarda bilişsel fonksiyonları değerlendirmeyi ve vitamin D düzeyi ile bilişsel fonksiyonlar arasında ilişki olup olmadığını araştırmayı amaçladık.…”
Section: Introductionunclassified